2024
DOI: 10.3389/fncel.2024.1335849
|View full text |Cite
|
Sign up to set email alerts
|

Reactive gliosis in traumatic brain injury: a comprehensive review

Zuzana Amlerova,
Martina Chmelova,
Miroslava Anderova
et al.

Abstract: Traumatic brain injury (TBI) is one of the most common pathological conditions impacting the central nervous system (CNS). A neurological deficit associated with TBI results from a complex of pathogenetic mechanisms including glutamate excitotoxicity, inflammation, demyelination, programmed cell death, or the development of edema. The critical components contributing to CNS response, damage control, and regeneration after TBI are glial cells–in reaction to tissue damage, their activation, hypertrophy, and prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 556 publications
0
6
0
Order By: Relevance
“…Not only did the number of TAAR1 + /GFAP + double positive cells increase (Figure 8I), but the ratio of TAAR1 + /GFAP + cells to TAAR1 + cells also increased (Figure 8J). These results indicated that TAAR1 levels were increased in the astrocytes within the OB and the PC in PD mice, which might modulate the enhancement of neuroinflammation in these regions [48].…”
Section: Taar1 Levels Increased In Astrocytes Within the Ob And The P...mentioning
confidence: 77%
See 1 more Smart Citation
“…Not only did the number of TAAR1 + /GFAP + double positive cells increase (Figure 8I), but the ratio of TAAR1 + /GFAP + cells to TAAR1 + cells also increased (Figure 8J). These results indicated that TAAR1 levels were increased in the astrocytes within the OB and the PC in PD mice, which might modulate the enhancement of neuroinflammation in these regions [48].…”
Section: Taar1 Levels Increased In Astrocytes Within the Ob And The P...mentioning
confidence: 77%
“…Consequent to these findings, the reduction of TAAR1 along the olfactory pathway in our study might result in Bcl-2/caspase-3 alterations and lead to neuronal damage. (2) Regulating the activity of astrocytes: Activation of TAAR1 in astrocytes significantly downregulates the level of the glutamate transporter EAAT-2, leading to an accumulation of glutamate and subsequent cytotoxicity [39,64] due to the corresponding influx of Ca 2+ into the cells to trigger apoptotic signals and the release of IL-1β, resulting in apoptosis and neuroinflammation [48]. The following two possible mechanisms are speculated according to previous reports and require further investigation: (3) Regulating the activity of microglia: Activation of TAAR1 in microglia can suppress the release of proinflammatory factors such as IL-6, TNF-α, NF-κB, MCP1, and MIP1, while simultaneously promoting the release of anti-inflammatory mediators like IL-10, thus fulfilling an anti-inflammatory role [40].…”
Section: Discussionmentioning
confidence: 99%
“…Despite ionic accumulation, AQP4 contributes to the cytotoxic and vasogenic edema due to increased expression and translocation from the astrocytic endfeet to the whole astrocyte, thereby causing intracellular fluid accumulation and astrocyte swelling ( Badaut, 2017 ). During TBI, microglia undergo morphological changes and become immunoreactive, which results in release of pro-and anti-inflammatory mediators ( Amlerova et al, 2024 ). This triggers immune cell migration from the periphery to the injury site through the disrupted BBB.…”
Section: The Pathophysiology Of Traumatic Brain Injurymentioning
confidence: 99%
“…Alterations in ion transport leads to opening of Ca 2+ channels, which causes further neuron depolarization, ultimately resulting in further glutamate release and intracellular fluid accumulation ( Zusman et al, 2020 ). The intracellular accumulation of Ca 2+ triggers apoptotic signals leading to cell death and release of inflammatory mediators eventually causing inflammation ( Amlerova et al, 2024 ). Neurons and oligodendrocytes are especially susceptible to apoptosis.…”
Section: The Pathophysiology Of Traumatic Brain Injurymentioning
confidence: 99%
See 1 more Smart Citation